Pengaruh Pendidikan Kesehatan Tentang Menstruasi Terhadap Kesiapan Psikologis Dalam Menghadapi Menarche Pada Remaja Putri Prapubertas Di SD Gugus V Mengwi - Ni Gusti Ayu Pramita Aswitami (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: Menarche is the first menstruation out in young women. Menarche occurs in young women who have entered the puberty phase. Often young women are not ready to face menarche, this is due to a lack of information about menstruation and preparations that must be done in the face of menstruation. With conditions that are not ready, young women often feel anxious and fearful, thus disrupting psychology and hindering daily activities. To prepare young women in the face of menarche, it is necessary to provide information correctly and right before teenage poetry enters puberty, the prepubertal period. This information can be provided through health education. through health education, young women are better prepared and not anxious and afraid when experiencing menarche. The aim of the study was to determine the effect of health education on menstruation on psychological readiness in the face of menarche in prepubertal adolescent girls in SD Gugus V Mengwi. Method: This research is a quasy-experimental study, the design of the research used is the Pre-test and Post-test One Group Design that is looking at the differences before and after the intervention. Samples taken were 79 class V students who had not experienced menarche at the SD Gugus V Mengwi V.The sampling technique is total sampling. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Statistical analysis using the Wilcoxon Match Pairs Test. Results : this study indicate that there is an influence of health education about menstruation on psychological readiness in the face of menarche in prepubertal girls in the Gwi Cluster V Elementary School. Conclusion: It is suggested to young women to increase their knowledge, awareness, and concern for the health of their reproductive functions, especially in the face of menarche after being given health education about menarche so that good readiness can be achieved when facing menarche.